A Generalization of $p$-Adic Factorial - Rafik Belhadef (Journal of New Theory)
In this paper, we establish a new approach of the p-adic analogue of Roman factorial, called p-adic Roman factorial. We define this new concept and demonstrate its properties and some properties of p-adic factorial.